the Kab Quarterly News Letter. Issues 07, October, 2023. - Kabale University (Kabale University, 2024)
We are pleased to share with you the seventh issue of the KAB Newsletter. Here is yet another collection of interesting news about the University. It is with great pleasure that we feature the Kagonyera family in this 7th issue. No doubt, this family has had a significant impact on the development of the Kigezi region as well as the professional landscape of Uganda. The university community, largely made up of staff, remains the major driving force behind campus and off-campus activities. It is important not to forget the other stakeholders that keep KAB's spirit alive in the community, such as our alumni. The day-to-day life around the university campus is also dominated by student activities. We hope you will enjoy this collection of stories. Our goal is to see greater growth in the amount of contributions they make to the newsletter. My sincere appreciation goes to the indefatigable team in the Communication, Branding, and Marketing Department who keeps track of the activities and document many of them. We are also grateful to the various individuals who allowed us the opportunity to interview them for some of the stories in this issue. Please accept my sincere thanks!